“You have to be Proactive with Your Child’s Health”: Learning and Health Literacy among Caregivers of Children with ADHD - Blaire W. Toso; Esther Prins; Kimeka Campbell; Barbara Schaefer; Dawn Witherspoon; Susan Woodhouse (Adult Education Research Conference, 2014)
This paper uses focus group data to examine health literacy among 26 low-socioeconomic status, minority caregivers of school-age children with ADHD. To cope with their child’s ADHD symptoms or diagnosis, caregivers used observation, gathered information from multiple sources, and discerned how to obtain services within confusing system healthcare and education systems.